Isolation, In Vitro Expansion, And Cryopreservation of Primary Cells Derived from Human Thyroid Carcinoma - Fatimah Eliana; Sabrina Azmi; Anggi Puspa Nur Hidayati; Juhan Khalila (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Thyroid carcinoma is a malignant neoplasm arising from thyroid parenchymal cells and currently ranks as the fourth most diagnosed cancer in Indonesia. This study aimed to isolate thyroid carcinoma cells for in vitro expansion and long-term preservation as a reliable cell culture stock, including cryopreservation for future research applications. In addition, we sought to identify and characterize cells derived from papillary thyroid carcinoma (PTC) tissue to evaluate the presence of mutations with potential prognostic significance. Primary cell isolation was performed via enzymatic digestion using collagenase, enabling effective separation of tumor cells from adjacent non-malignant thyroid tissue. Cell proliferation was supported using Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 20% fetal bovine serum (FBS), selected for its high concentration of growth-promoting factors that enhance proliferation rates. For biobanking purposes, cryopreservation of the thyroid carcinoma-derived cells was conducted using a standard slow-freezing protocol. Molecular characterization was carried out through PCR amplification, gel electrophoresis, and Sanger sequencing of key oncogenic drivers, specifically the BRAF gene and five RAS gene targets: HRAS exon 2, NRAS exons 2 and 3, and KRAS exons 2 and 3. No pathogenic mutations were identified in the analyzed BRAF or RAS gene regions.